Benturan Kepentingan pada Pendanaan Pilkada - Dalilah, Elih; Selawati, Bekti; Pratama, Fitrah; Wijayanti, Anis (Integritas : Jurnal Antikorupsi, 2019)
Funders take a role in resolving the problem of large regional election cost gaps and insufficient wealth of candidates for regional head elections. However, the hope of the funder will reciprocate the contribution that has been given to cause a problem of conflict of interest by the elected regional head. The KPK conducted a study to identify potential conflicts of interest in regional election funding. The study was conducted on the losing head/deputy regional head candidates in 2015, 2017 and 2018 regional elections through the telescopic method, secondary data processing (KPU and LHKPN), and special in-depth interviews in 2018. Studies show that the hopes of funders will return in the future clearly expressed. Most of the candidates for head/deputy regional head will meet these expectations when winning the election/office. Funders expect a response in the form of business licensing, ease of participating in government project tenders, and security in conducting business. Keywords: Conflict of Interest, Corruption, Local Election